NATURE AS A SPIRITUAL VALUE IN ESTABLISHING OF THE CULTURE OF UKRAINIAN MODERN SOCIETY - Мокляк, Л. І.; Покотило, Г. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article investigates the place and role of nature in the system of spiritual values of culture in Ukrainian modern society.